Emergency department presentation following falls: development of a routine falls surveillance system. Issue 1 (5th October 2010) - Johansen, A; Dickens, J; Jones, M; Richmond, P; Evans, R
Abstract : Introduction: Falls are recognised as a major public health issue, particularly among older people, and have been targeted for attention by national service frameworks and National Institute for Health and Clinical Excellence guidelines in the UK. However, reliable epidemiological data are not easily available, and it remains difficult to monitor the effect of interventions that seek to reduce the public health impact of falls. Method: In a 1-year study based in the emergency department (ED) of the University Hospital of Wales all Cardiff residents who described their presentation as following a fall were identified. From a catchment population of 305 353 people a total of 86 031 such ED presentations were recorded, 20 154 (23.4%) of which followed a fall. Results: This gives an overall falls incidence of 66/1000 population per year, meaning that in just a year one resident in 15 attended the ED following a fall. The impact of falls was greatest in the oldest age groups, and in women aged over 75 years the falls incidence of 139/1000 per year was significantly higher than the figure of 99/1000 per year observed in men of the same age. Conclusions: This study describes a simple way for ED to establish routine falls surveillance. It offers the first estimate of the impact of falls on ED in the UK, suggesting that such services are dealing with 4 million falls-related attendances every year.